Evaluation of three doses of the biostimulant Chitosana in the cucumber (Cucumis sativus) crop in a late period - González-Gómez, Luis Gustavo (2012)
This study investigated the efficacy of a  biostimulant produced by the National Insitute of Agricultural Sciences in Cuba, named Quitosana, in the cultivation of cucumber, Cucumis sativus. One planting bed per treatment was selected as an experimental unit, with a population of 207 plants, planted in double rows 30 cm apart. The cucumber variety used was SS-5. The bioactaive compound Quitosana was applied in the foliar form in the early hours of the morning, 10 days alter seed germination. Crop propagation was done by direct planting. The experiment included 4 treatments, which consisted of three doses and one control. Different reproductive parameters were evaluated in the first harvest of the cucumber crop, leading to important conclusions about the effects of the evaluated doses on the growth and development of the crop.